Alternative and activist new media - Lievrouw, Leah A. (Cambridge, UK : Polity, 2023)
Introduction: Activism in the age of algorithmic media - New media activism: art and design influences - New media activism social movement theory - A genre framework for alternative and activist media - Speaking noise to power: culture jamming - The culture of creative disobedience: alternative computing - Algorithms and citizens: participatory journalism and OSINT - "Be water": mediated mobilization - Defying the informatics of domination: common knowledge - Conclusion: Recovering knowledge and trust .
Keywords: Communication -- Political aspects; Mass media -- Politicl aspects; Web 2.0 -- Political aspects; Political campaigns; Counterculture